B-Myb, Cancer, Senescence, and MicroRNAs - Martinez, Ivan (2011)
The transcription factor B-Myb plays a critical role in regulating gene expression and is implicated in controlling carcinogenesis and cellular senescence. Transcription of the B-Myb gene is regulated by retinoblastoma proteins acting directly on the B-Myb promoter. Recently, we found that microRNAs also control the abundance of B-Myb mRNA during senescence, adding another level of complexity to B-Myb regulation. This review focuses on the importance of B-Myb in cancer and senescence, with an emphasis on the regulation of B-Myb expression and activity.